The Simile Word (Kaaf Al-Tashbeeh) Between The Stability, Problem Of Definition, And Significance - Mesfer Mihmas Aldawsari (Ijaz Arabi Journal of Arabic Learning, 2023)
The Arabic letter "Kaaf" has multiple meanings. It's also a noun. There are several types of "Kaaf" in Arabic, but the "Kaaf al-Tashbeeh" is the most controversial. Some claim it's a "noun," and others say it's a "particle," while others try to reconcile the two by saying it's a "noun" in some circumstances and a "particle" in others. Some linguists say it's exclusively used for "simile," while others say it has various connotations. The research methods employed in this study are the descriptive analytical approach, contemporary Arabic grammar texts, and linguistic sources. This study seeks to understand why the letter "kaaf" has different meanings. The first section addressed the perspective of grammarians that "Kaaf al-Tashbeeh" is a particle and their arguments. The second section explored grammarians' justifications for calling it a "noun" The final section presents the stance of grammarians and linguists who seek a middle ground. According to linguists and grammarians, the expected outcome of the research is that the letter "kaaf" is undoubtedly a noun. It makes no difference if the characteristics of "nouns" set by the grammarians don't apply to it because many "nouns" don't have those characteristics, but no one disputes their being "nouns."